(3QSGdI aj Mce dHS GdSfLGH aj GdUdGI hNGQLgG Ydi GdePgH GdTGaYis - (3CHj HcQ Hf hdj GdOjf Hf bGVj YLdhf GdTGaYj, Jbj GdOjf,J (B928 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdgGOi Edi GdUhGH s
(3BNQgG (B:s
(3fSCd Gddg JYGdi ef aVdg GdJhajb deG jQVGg hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg CLejYf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP GdOcJhQ ESMGb ehSi GdMSjfi GdNGUI s
Keywords: (3Gdabg GdTGaYjs